Gallery 2: Bolswert in Quito: The Series on the Life of Saint Augustine by Miguel de Santiago - Ojeda, Almerindo E. (2014)
A series of twenty eight engravings on the Life of Saint Augustine appeared in Antwerp in 1624. The engravings were bound in a volume entitled Iconographia magni patris Aurelii Augustini. The work was commissioned by Georges Maigret, prior of the hermitage of Malines (Mechlen), in Flanders, who wrote the texts accompanying the images. Of the twenty eight engravings in the volume, twenty six were done by Schelte à Bolswert, one of the most distinguished members of the Antwerp school of engravers. The author of the other two was Cornelis Galle. A distinguished engraver in his own right, Galle was a regular collaborator of Bolswert. The Augustinian series of Bolswert and Galle exerted tremendous influence around the world. In the Americas it served as a model to several series on the life of Saint Augustine. One of the most important ones is found in the Convent of Saint Augustine in Quito, Ecuador (Gillet 1929, 1070; Vargas 1944, 117ff; Navarro 1950, 85-96; Courcelle and Courcelle 1972, Volume III, Chapter VII), where it is displayed in an ornate gold-leaf framework (see above). The Quito series was produced by Miguel de Santiago and his workshop in 1656. Although the series by Bolswert and Galle served as the basis for their compositions, it is clear that they relied on other sources as well. The painting above, for example, is not based on the Antwerpian series. It is also possible that the series currently displayed is incomplete, as it is missing important scenes found in the series by Bolswert and Galle--the Baptism of Augustine, for one, and his Investiture for another. We have collected in this gallery the correspondences between the Bolswert-Galle series and the group of paintings by Miguel de Santiago. To visit this gallery, follow the navigation panel below throughout this website. Click on the down-arrows to move through the gallery; to retrace your steps, click on the up-arrows.